Prevalence of abnormal Pap smear during pregnancy in a teaching hospital in South India - Mishra, Varsha; Dorairajan, Gowri; Neelaiah, Siddaraju; Chinnakali, Palnivel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of cancer cervix is very high in our country. Women in our country typically present late when the disease is advanced. Screening during pregnancy gives an opportunity to pick up at pre-invasive/early stage as women come voluntarily seeking health care to hospitals. Abnormal cervical cytology is also associated with increased risk of adverse pregnancy outcome. This study was undertaken to determine the prevalence of abnormal Pap smear among pregnant women. Methods: This cross sectional study was carried out in a teaching institution among pregnant women using conventional cytology (with Ayer’s spatula) reported by Bethesda system after obtaining informed consent. The study was approved by institute ethics committee. Results: Among the 316 women studied the mean (SD) age at marriage was 22 (3) years. The mean period of gestation was 30 weeks. Only one participant (0.3%) reported high risk behaviour. The speculum examination was found to be normal in 99.7% women. There was one abnormal Pap smear report. Specific infection with Candida was reported in 14.6%; in none of these the speculum examination showed a characteristic discharge of candidiasis. Further a significantly higher prevalence of Candida infection was found in rural compared to urban population (Chi square 3.7, p=0.046). Conclusions: The prevalence of abnormal Pap smear is particularly low at 0.3% in our study group. However the prevalence of asymptomatic Candida infection which was missed on speculum exam because of lack of the characteristic discharge was high at 14.6%. Thus the authors recommend routine prenatal microbiological examination to detect candida infection.